2020
DOI: 10.3389/fnbot.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Robot-Assisted Lower-Limb Stroke Therapy: Unexplored Paths and Future Directions in Gait Rehabilitation

Abstract: Stroke affects one out of every six people on Earth. Approximately 90% of stroke survivors have some functional disability with mobility being a major impairment, which not only affects important daily activities but also increases the likelihood of falling. Originally intended to supplement traditional post-stroke gait rehabilitation, robotic systems have gained remarkable attention in recent years as a tool to decrease the strain on physical therapists while increasing the precision and repeatability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 191 publications
(150 reference statements)
0
93
0
2
Order By: Relevance
“…Due to portability and excellent temporal and spatial resolution of both EEG and fNIRS helping patients during gait rehabilitation in terms of wearable lower limb exoskeletons, orthosis, prosthesis, and other assistive robotic devices (Belda-Lois et al, 2011 ; Chéron et al, 2012 ; Castermans et al, 2013 ; Tariq et al, 2018 ; Hobbs and Artemiadis, 2020 ). Belda-Lois et al ( 2011 ) reviewed gait therapies used in gait rehabilitation comprise classical gait rehabilitation techniques, FES, BCI systems, and assistive robotic devices.…”
Section: Hybrid Eeg-fnirs-based Bcimentioning
confidence: 99%
“…Due to portability and excellent temporal and spatial resolution of both EEG and fNIRS helping patients during gait rehabilitation in terms of wearable lower limb exoskeletons, orthosis, prosthesis, and other assistive robotic devices (Belda-Lois et al, 2011 ; Chéron et al, 2012 ; Castermans et al, 2013 ; Tariq et al, 2018 ; Hobbs and Artemiadis, 2020 ). Belda-Lois et al ( 2011 ) reviewed gait therapies used in gait rehabilitation comprise classical gait rehabilitation techniques, FES, BCI systems, and assistive robotic devices.…”
Section: Hybrid Eeg-fnirs-based Bcimentioning
confidence: 99%
“…The use of robot-assisted gait training has been one of the most current studies in the field of rehabilitation, showing itself as a promising area [94][95][96][97]. In [98], the authors reported an initial study to analyze the emotion of patients, offering a therapist a better interpretation of the psychological state of the patient and their transition from each emotional state.…”
Section: Systems and Sensors In Physical Rehabilitationmentioning
confidence: 99%
“…Some of these directions that more directly relate with motion rehabilitation [ 4 , 10 , 11 ] are: To assess the effects of using robots at different phases of recovery. To develop wearable robots easy and practical to wear and remove.…”
Section: New Directions To Explore and Open Problems: Aims Of The mentioning
confidence: 99%